(untitled) (Altifani : Jurnal Pengabdian Masyarakat Ushuluddin, Adab, dan Dakwah, 2026)
Administrative management in Al-Qur’an Education Centers (TPQ) is often neglected due to human resource constraints and reliance on manual systems prone to data damage. This community service aims to transform conventional administration into a digital system at TPQ Al-Wasari, Mata Ie Village, Southwest Aceh. Using the Participatory Action Research (PAR) method through technical assistance, this service involved preparation, training on integrated digital systems, and evaluation. The results show that the implementation of registration forms, online attendance, and cloud-based archiving significantly improved operational efficiency and data accuracy. This digitalization not only enhances the professionalism of the institution but also strengthens parents’ trust in TPQ management in the Society 5.0 era.